On the Way to BRICS+ Digital Sovereignty: Opportunities and Challenges of a New Era - E. Gromova; D. Brantes Ferreira (BRICS Law Journal)
A new era for BRICS has begun with the desire of new countries to join BRICS. This expansion, the BRICS+, poses several challenges and opportunities for the renewed alliance, particularly concerning the digital sovereignty of the countries. On the one hand, the leading five BRICS nations have the potential to achieve digital sovereignty, earning the moniker “the hawks of digital sovereignty.” On the other hand, expanding BRICS membership to countries with varying levels of digitalization raises issues for the alliance. These include improving national legislation on digital sovereignty and defining actions to foster cooperation within BRICS+. This article aims to design a theoretical legal model for BRICS+ digital sovereignty, outlining its pillars and offering recommendations for achieving digital sovereignty within BRICS+. The comparative legal method, used to analyze regulations in digitalization and digital sovereignty among BRICS+ member countries, ensures a comprehensive understanding of the legal landscape. Retrospective analysis, which studied the development of BRICS+ regulations in these areas, provides a historical context. The systematic method, which examined legal tools and instruments that contribute to achieving digital sovereignty, ensures a thorough exploration. The content analysis allowed for the interpretation of news articles and social media sources related to BRICS+ digital sovereignty, adds a contemporary perspective. The authors conclude that achieving digital sovereignty for BRICS+ is possible and offer several recommendations for collaboration, including developing a BRICS+ digital sovereignty memorandum, launching a BRICS+ regulatory sandbox, and deploying a BRICS+ sovereign cloud. These recommendations can inform BRICS+ policy-making, contribute to the limited literature in this field, and serve as a basis for future research on BRICS+ digital sovereignty.